1998
DOI: 10.1183/09031936.98.12061415
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of bronchial biopsy rinse fluid to improve the diagnostic yield for lung cancer

Abstract: Sampling techniques are combined during bronchoscopy to increase the diagnostic yield for endobronchial malignant tumours. Bronchial biopsy provides the definitive histological diagnosis in most cases, but accompanying cytological procedures such as washing, brushing, needle aspiration or imprint cytology can increase diagnostic yield. In this prospective study, a different cytological technique, that could enhance the diagnostic yield of bronchoscopy without increasing its time or cost, was tested. Flexible b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
2
22
0
1
Order By: Relevance
“…[17] Despite the numerous advantages of CBs, the cellular yield of CBs is inconsistent and varies widely. [181920]…”
Section: Discussionmentioning
confidence: 99%
“…[17] Despite the numerous advantages of CBs, the cellular yield of CBs is inconsistent and varies widely. [181920]…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these techniques were not analysed separately, so no conclusive results could be obtained from Zavala's report. Cytological examination of the rinse fluid of biopsy specimens had not been mentioned again until 1998, when Rosell et al (1998) evaluated the effectiveness of this technique. They reported that this technique increased the diagnostic sensitivity of lung cancer from 65.8 to 70.7% (P ¼ 0.009).…”
Section: Discussionmentioning
confidence: 99%
“…The cytological examination of the brushing samples or bronchial washing fluid in addition to the histological examination of specimens obtained by forceps biopsy has been shown to increase sensitivity in the diagnosis of peripheral lung tumour, by an estimated 12 -30% (Chaudhary et al, 1978;Mak et al, 1990;Govert et al, 1996). Furthermore, cytology on the rinse fluids has been previously reported to elevate the diagnostic sensitivity from 65.8 to 70.7% (Zavala, 1975;Rosell et al, 1998). On the basis of these results, we planned to evaluate the effects of a histological examination combined with cytological techniques such as imprints of biopsy specimens and cytology on the rinse fluids of the forceps and brush; the effects of such combinations have not been previously reported.…”
mentioning
confidence: 99%
“…The commonly used method of CB preparation is to rinse the aspiration needle with normal saline, spin down and collect the material, and then process the pellet in the laboratory 24‐27. Our experience, and that of others, has shown that a variable amount of material and/or tissue is recovered using this conventional method, and the efficiency of this method for obtaining adequate tissue samples is limited 23‐27.…”
Section: Introductionmentioning
confidence: 99%